A systematic review of negative parenting practices predicting borderline personality disorder: Are we measuring biosocial theory's 'invalidating environment'?. (November 2018) - Musser, Nicole; Zalewski, Maureen; Stepp, Stephanie; Lewis, Jennifer
Abstract: A core tenet of Linehan's biosocial theory (1993) is that borderline personality disorder (BPD) emerges as a result of transactions between emotional vulnerability and an invalidating environment. Invalidation has become a popular term in the literature, but there is a lack of uniformity in its operationalization and measurement, particularly as applied to invalidating parenting practices that are non-abusive. This systematic review of 77 empirical studies examined the measurement and operationalization of parental invalidation in the BPD literature and determined the extent to which measurements used converge with Linehan's original model. This review provides a description of methodological design features of the literature and presents the percent of studies that measured four key components of invalidation—inaccuracy, misattribution, discouragement of negative emotions, and oversimplification of problem solving. Limitations of the literature, including a dearth of studies which include measurements that align with Linehan's model, and recommendations for future research are discussed in an attempt to encourage greater scientific rigor in the measurement of invalidation and elucidate the role of invalidation in the development of BPD. Highlights: Linehan's biosocial theory posits the invalidating environment is at the core of the development of borderline personality disorder (BPD). This systematic review identified studies that measured the invalidating environment or poor parenting and BPD outcomes to determine if how the field measures the invalidating environment aligns with Linehan's model. Of the 77 studies identified, 47 different measures exist to assess poor parenting in relation to BPD. Greater uniformity is needed about how to measure poor parenting or the invalidating environment in order for the field to quantify the extent to which these types of specific factors contribute to BPD.